LANGXIAN'S DILEMMA OVER THE CULT OF MARTYRDOM AND FILIAL PIETY: A WORLD OF EMPTINESS IN "THE SIEGE OF YANGZHOU". (November 2015) - Wang, Xian
Abstract : Ming vernacular stories are filled with images of martyrdom. The authors of these stories typically present positive images of suicide that support the neo-Confucian valorization of martyrdom for the sake of female chastity, filial piety, and political loyalty. In "The Siege of Yangzhou" and within the entire late-Ming Shi dian tou collection, the author Langxian rejected the dominant cultural ideal of martyrdom as sublime. Langxian expanded his text from previous versions of the same story, and through the ruptures and puzzling narrative discontinuities introduced into his rewriting of the text an undermining of the moral value of the protagonist's gruesome martyrdom. This story is an ironic deflation of female martyrdom that goes against the current view of Langxian as a conservative adherent of neo-Confucian ideology.